Analiza deformacij vrtal po analitični metodi in s končnimi elementi - Taşkesen, Ahmet (Strojniški vestnik, 2006)
In this paper we discuss the deformation analyses of boring bars using analytical and finite-element methods. Three types of circular boring bars with HSS and cemented-carbide properties were selected, and their deformations when subjected to oblique boring forces were calculated using both methods. A guideline is proposed for the manufacturer, who can determine the extent of the errors that affect the dimensional tolerance and the surface-finish accuracy of the bored hole produced by the bar bent when subjected to the boring forces. Also, we observed that a conical bar is not anappropriate design for boring a long hole.
Keywords: procesi vrtanja; analize deformacij; metode končnih elementov; svedri; deformacije; finite element method; metoda končnih elementov